ANALYSIS PRAGMATIC STUDY ON DEIXIS IN THE ARTICLES JAKARTA SPORT - Resti Nur Setiakawanti; Elsa Susanti (IKIP Siliwangi, 2018)
The purpose of this research is to identify deixis forms and meanings used in Jakarta post articles. This study was applied qualitative descriptive. Then, it was analyzed by using the Dylgjeri and Kazazi concept the data was table from in article Jakarta Post. The findings indicate that the types of deixis found in articles selected from the Jakarta Post are the first person there are I, Me, My, We, and Our (In third person there are She, Her, His, Him, and They), deixis spatial (there are school, class, hospital, on the stairs, world, here and there.), and temporal deixis. (there are now, then, five month ago, today, and yesterday). The results of this study show that person deixis is used 157 times and have percentage 66.5% spatial deixis is used 54times and have percentage 22.8% and temporal deixis is used 25times and have percentage 10,5% Keywords: Pragmatic, Deixis